2008
DOI: 10.2466/pms.106.3.963-966
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Upper Extremity Kinesthetic Sense and Writing Performance by Students with Low Vision

Abstract: Kinesthetic sense plays an important role in writing. Children with low vision lack sensory input from the environment given their loss of vision. This study assessed the effect of upper extremity kinesthetic sense on writing function in two groups, one of students with low vision (9 girls and 11 boys, 9.4 +/- 1.9 yr. of age) and one of sighted students (10 girls and 10 boys, 10.1 +/- 1.3 yr. of age). All participants were given the Kinesthesia Test and Jebsen Hand Function Test-Writing subtest. Students with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…But none of these scales have been standardized in children with low vision. Aki, Atasavun, and Kayihan (2008) successfully used the Jebsen-Taylor Hand Function Tests-Writing subtest in the children with low vision.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But none of these scales have been standardized in children with low vision. Aki, Atasavun, and Kayihan (2008) successfully used the Jebsen-Taylor Hand Function Tests-Writing subtest in the children with low vision.…”
mentioning
confidence: 99%
“…The common finding of these researchers was that the writing performance of children with motor retardation was worse than that of their non-impaired peers (Feder et al, 2005;Engel-Yeger, Nagauker-Yanuv, & Rosenblum, 2009;Bumin & Kavak, 2010); Klein, et al (2011) further stated that children with learning and behavioral impairments had handwriting problems. Nevertheless, research in children with low vision and therefore a sustained lack of sensory input is very limited (Aki, et al, 2008;Reimer, Cox, Nijhuis-Van der Sanden, & Boonstra, 2011). Aki et al (2008) evaluated writing performances between children with low vision and their peers, and they found that low-vision children had lower performance times than their peers (Aki, et al, 2008 Due to the lack of visual clues for children with low vision during handwriting activities, results may differ from those in students without visual impairment, due to the effect of visual-motor control on the writing skill components of children with low vision.…”
mentioning
confidence: 99%
“…It is comprised of seven subtests for both the nondominant and dominant hands: writing, simulated page turning (ST1), lifting small objects (ST2), simulated feeding (ST3), stacking checkers (ST4), lifting large light objects (ST5), and lifting large heavy objects (ST6). We elected not to use the writing subtest since children with low vision have been shown to perform poorly on this task (Aki et al, 2008), the subtest has multiple limitations (Beebe & Lang, 2009; Schaefer et al, 2018; Sears & Chung, 2010), and the skill being tested minimally translates to typical ADLs anticipated for the CLN3 cohort. Subtest scores (time in seconds to complete the task) and a total score (sum of scores for ST1–ST6) are calculated (Taylor et al, 1973), with higher scores indicative of slowed/impaired function.…”
Section: Methodsmentioning
confidence: 99%
“…The integration of sensory and motor systems is essential in the development of goal-directed action in infants ( Ferronato et al, 2014 ) and children’s hand movements have not completed full maturation yet ( Rueckriegel et al, 2008 ). Furthermore, children with visual impairment often show delayed motor development ( Reynell, 1978 ; Sleeuwenhoek and Boter, 1995 ; Bouchard and Tetreault, 2000 ; Brambring, 2001 ; Celeste, 2002 ; Aki et al, 2008 ; Houwen et al, 2008 ; Reimer et al, 2008 ; Grant and Moseley, 2011 ; Lions et al, 2013 , 2014 ) which might affect their ability to control the magnifier. The complexity of the task relates to the required level of motor and cognitive abilities ( Schurink et al, 2011 ); a static task requires a lower level of motor and cognitive abilities than a dynamic task that entails simultaneous control of multiple action parameters.…”
Section: Introductionmentioning
confidence: 99%
“…First, we hypothesized that visually impaired children would need more time than normally sighted children in Phase 1, which primarily involves goal-directed arm movements with the LVA. This hypothesis was based on studies showing that fine and gross motor skills and goal-directed movements are less well developed in children with visual impairment than in children with normal vision ( Reynell, 1978 ; Sleeuwenhoek and Boter, 1995 ; Bouchard and Tetreault, 2000 ; Brambring, 2001 ; Celeste, 2002 ; Aki et al, 2008 ; Houwen et al, 2008 ; Lions et al, 2013 ; Liebrand-Schurink et al, 2015 ) Second, we hypothesized that visually impaired children would need more time to identify a symbol under threshold than normally sighted children in Phase 2, because they have less experience with small details. Young children are used to accommodate when stimulated with details.…”
Section: Introductionmentioning
confidence: 99%